Evaluasi Keterampilan Komunikasi Interpersonal antara Konselor dengan Siswa, Staf Sekolah, dan Orangtua di SMKN Kota Malang - Galang Surya Gumilang (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2015)
This study aimed to evaluate the skills of interpersonal communication between counselors and students, school staff, and parents. The approach used mixed method, with the type of evaluation research. The research instrument consisted of a questionnaire interpersonal communication skills and interview guides interpersonal communication skills. Subject of research is three counselors in one of SMK Negeri Malang. The results showed that interpersonal communication skills counselors with students, school staff, and parents are performing well with an average percentage score of 81.7%. The results of this study helpful for counselors as consideration in the development of interpersonal communication skills. Therefore, it is expected for counselors in order to continue to develop interpersonal communication skills with students, school staff, and parents through training / workshops.